2015
DOI: 10.3758/s13423-015-0944-y
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of task-set carry-over: evidence from eye-movement analyses

Abstract: Trial-to-trial carry-over of task sets (i.e., task-set inertia) is often considered as a primary reason for task-switch costs. Yet, we know little about the dynamics of such carry-over effects, in particular how much they are driven by the most recent trial rather than characterized by a more continuous memory gradient. Using eye-tracking, we examined in a 3-task, task-switching paradigm whether there is a greater probability of non-target fixations to stimuli associated with the previously relevant attentiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 21 publications
3
14
0
Order By: Relevance
“…For example, the timing of the target/distractor location representations is highly consistent with recent work using eye-tracking to assess the dynamics of attentional allocation to task-relevant and irrelevant features (12,23). More importantly, our results also reveal the time course for both cue and task representations.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…For example, the timing of the target/distractor location representations is highly consistent with recent work using eye-tracking to assess the dynamics of attentional allocation to task-relevant and irrelevant features (12,23). More importantly, our results also reveal the time course for both cue and task representations.…”
Section: Discussionsupporting
confidence: 89%
“…After initial preprocessing and identification of artifacts (see SM), the single-trial EEG data were decomposed into a time-frequency representation via wavelet decomposition (for details see SM). For simplicity we focused on frequency bands that are most often presented in the literature: delta (2-3 Hz), theta (4-7 Hz), alpha (8)(9)(10)(11)(12), and beta (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31). For each frequency band, we averaged the power signal across the range of interest.…”
Section: Eeg Decoding Analysesmentioning
confidence: 99%
“…We used a cued task switching paradigm that was closely modelled after a paradigm that we had previously used in the context of eye-tracking experiments 12,26 . On each trial, an auditory cue indicated which of the tasks, the Color task or the Orientation task, participants had to complete.…”
Section: Methodsmentioning
confidence: 99%
“…The experiment began with two single-task practice blocks (one for each task, order counter-balanced), and a task-switching practice block (20 trials), followed by 22 test blocks of 64 trials each. In order to incentivize participants to respond quickly and accurately, they were rewarded a small amount (0.5 cents) for each trial where they were faster than the 75 th % percentile of their RT distribution up to that point, but only if they maintained at least 90% accuracy for a given block 26 . At the end of each block, subjects were given feedback about their average RT and accuracy for that block.…”
Section: Methodsmentioning
confidence: 99%
“…Specifically, disengagement may support breaking mental set by allowing novel combinations of information to be generated (Oberauer et al, 2007). Higher AC may improve the integrity of this process by mitigating attentional capture at a time when PM is susceptible to intrusion from SM (Cosman & Vecera, 2013;Dreisbach & Wenke, 2011;Kikumoto, Hubbard, & Mayr, 2016;Mayr, Kuhns, & Hubbard, 2014;Richter & Yeung, 2012;Robison & Unsworth, 2017). Therefore, it was hypothesized that PM would be positively related to breaking mental set, but only for individuals with higher AC.…”
Section: Discussionmentioning
confidence: 99%